Serendipity as a mechanism of change and its potential for explaining change processes - Ursula Weisenfeld-Schenk (Management Revue, 2009)
Serendipity plays an important role in science and technology development. This article investigates serendipity as a potential mechanism of change in management areas such as technology management, strategy and organization. The mechanism will be described and conditions that support or hinder the mechanism will be discussed.
Keywords: 650; mechanisms of change; serendipity; organizational change; strategic change; technological change